Imagining histories of colonial Latin America : synoptic methods and practices - Melvin, Karen (Assistant Professor of History); Sellers-García, Sylvia; Carrasco, Davíd (Religions of the Americas series, 2017)
Imagining Histories of Colonial Latin America teaches imaginative and distinctive approaches to the practice of history through a series of essays on colonial Latin America. It demonstrates ways of making sense of the past through approaches that aggregate more than they dissect and suggest more than they conclude. Sidestepping more conventional approaches that divide content by subject, source, or historiographical "turn," the editors seek to take readers beyond these divisions and deep into the process of historical interpretation. The essays in this volume focus on what questions to ask, what sources can reveal, what stories historians can tell, and how a single source can be interpreted in many ways.